Analysing Challenges Faced by Micro Finance Institutions and Exploring Linkages on Rural Development and Quality of Life - Monish P (Jurnal Multidisiplin Madani, 2024)
Micro finance institutions play a significant role in economic development of India. Such institutions provide financial access to lower income people. These institutions are very helpful for poor people who lack access of banking services. Micro finance institutions provide a large variety of financial and non-financial services to people including credit, counseling, and training. Such institutions are necessary to achieve rural development, financial inclusion and women empowerment.  Today micro finance institutions are faced many problems. Problems of non-performing assets are considered as a big challenge for micro finance institutions. Financial illiteracy, lack of speedy generation of funds, lack of proper infrastructure, political interference and competition are the other challenges faced by micro finance institutions. This chapter made an attempt to analyze the problems faced by micro finance institutions and understand the role of micro finance in rural development